2021
DOI: 10.1111/tri.13926
|View full text |Cite
|
Sign up to set email alerts
|

Early perioperative fluid overload is associated with adverse outcomes in deceased donor kidney transplantation

Abstract: Kidney transplant recipients are often treated with a large volume of infusion to attain adequate graft perfusion in the early perioperative period. However, it remains unknown whether this fluid therapy is renal responsive or a contributing factor to fluid overload complications. We conducted a retrospective cohort analysis of all recipients who received deceased donor kidney transplantation at an academic teaching hospital from January 2015 to April 2019. Our exposure of interest was early perioperative flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Fluid management is one such factor. In adult transplant recipients, judicious use of fluids was found to be beneficial [ 4 , 5 ], but there is a high degree of variability in fluid management strategies used, with no consensus on the most advantageous approach [ 6 ]. There is also a paucity of high-quality evidence to guide optimal perioperative fluid management in children receiving kidney transplants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid management is one such factor. In adult transplant recipients, judicious use of fluids was found to be beneficial [ 4 , 5 ], but there is a high degree of variability in fluid management strategies used, with no consensus on the most advantageous approach [ 6 ]. There is also a paucity of high-quality evidence to guide optimal perioperative fluid management in children receiving kidney transplants.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 4. Comparison between the median volumes of fluid administered in total in ml/kg between children who did or did not experience an adverse event during the postoperative period…”
mentioning
confidence: 99%
“…Optimum perioperative fluid administration with adequate intravascular volume maintenance is essential to improve outcomes in critically ill patients, prevent acute organ failure or dysfunction, and improve immediate graft function after KTA and SPKT [ 19 , 21 , 31 , 32 , 33 , 34 , 35 ]. Determination of the perfect amount of fluid therapy is highly challenging in critically ill patients, as well as in the perioperative phase during operations with a high fluid turnover.…”
Section: Discussionmentioning
confidence: 99%
“…However, analyzing data from a cohort of first deceased-donor KT recipients, an elegant study from the University Hospital of Gent, demonstrated that pre-transplant PD and optimized (slightly positive) peri-operative fluid balance were independent predictors of immediate graft function [107]. As a matter of fact, recent data indicate that graft function is more likely affected by intra-operative and early post-operative fluid loads rather than by chronic hydration [108,109]. The RRF at the time of transplant may also play a role [110,111].…”
Section: Delayed Graft Functionmentioning
confidence: 99%